Integration of Physical Education and Mental Health in Adolescents: An Evidence-Based Literature Review - Sahabuddin, Sahabuddin; Syahruddin, Syahruddin (Journal of Sport Education, Coaching, and Health (JOCCA), 2025)
The integration of Physical Education (PE) and mental health promotion in adolescents has become a growing focus in educational and public health discourse. This evidence-based systematic literature review aims to explore the impact of school-based PE programs on adolescent mental health, highlighting effective integration models, mediators, and challenges. Using six databases (Scopus, PubMed, ScienceDirect, Google Scholar, DOAJ, and Garuda), twenty peer-reviewed articles published between 2014 and 2024 were identified and analyzed thematically and narratively. Findings consistently demonstrate that regular participation in structured PE is associated with reduced levels of depression (SMD = -0.64; p < 0.01), anxiety, and stress, and enhanced well-being, self-esteem, and resilience. For instance, a meta-analysis by Lubans et al. (2016) revealed that school-based physical activity significantly improved psychological well-being across 14 controlled studies. The effectiveness of these interventions is moderated by factors such as gender, age, frequency, and duration of activity, and social support. Programs integrating mindfulness, cooperative games, and sport-based counseling were found particularly effective. Despite promising outcomes, several barriers hinder implementation, including a lack of teacher training, weak institutional support, and prevailing stigma toward mental health in schools. Multi-component interventions—merging PE with counseling, mental health education, and teacher capacity building—are crucial for sustainable outcomes. This review emphasizes the importance of embedding mental health promotion within PE curricula to support holistic adolescent development and calls for future policies to prioritize integrative, evidence-based approaches.